1996
DOI: 10.1111/j.1600-0404.1996.tb07035.x
|View full text |Cite
|
Sign up to set email alerts
|

HMPAO SPECT in non-epileptic seizures: preliminary results

Abstract: The diagnosis of non-epileptic seizures (NES) is problematic. Although diagnosis can be achieved by videotelemetry, these facilities are expensive and not widely available. HMPAO SPECT studies show focal hypoperfusion interictally in focal epilepsy. SPECT has not been studied in any detail in NES previously. Two groups (10 patients each) were studied, one with NES and one with complex partial seizures and localisation related epilepsy. SPECT scans were normal in 7 of 10 (70%) NES patients, while showing clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
1
17
0
4
Order By: Relevance
“…A number of studies have described cases in which ictal/interictal-SPECT was performed on patients with PNES. In the majority of cases SPECT results were negative, and in some cases a positive result was found, though the locations were not consistent across studies (Biraben et al, 1999;Ettinger et al, 1998;Neiman et al, 2009;Spanaki et al, 1999;Varma et al, 1996). Another study reported that group analysis of patients with PNES revealed significant PET hypometabolism within the right inferior parietal and central area, and within the bilateral anterior cingulate cortex (Arthuis et al, 2014).…”
Section: Increased Fa In Superior Temporal Gyrus (Stg)mentioning
confidence: 88%
“…A number of studies have described cases in which ictal/interictal-SPECT was performed on patients with PNES. In the majority of cases SPECT results were negative, and in some cases a positive result was found, though the locations were not consistent across studies (Biraben et al, 1999;Ettinger et al, 1998;Neiman et al, 2009;Spanaki et al, 1999;Varma et al, 1996). Another study reported that group analysis of patients with PNES revealed significant PET hypometabolism within the right inferior parietal and central area, and within the bilateral anterior cingulate cortex (Arthuis et al, 2014).…”
Section: Increased Fa In Superior Temporal Gyrus (Stg)mentioning
confidence: 88%
“…Quantitative SPECT, apart from a role in lesion localization for epilepsy surgery, has been used in cases where there is diagnostic uncertainty despite video EEG. 46 While ictal/interictal and subtraction SPECT are typically normal in PNES patients, 47 focal insular hypermetabolism on subtraction ictal SPECT 46 and bilateral frontal and right medial temporal lobe hypometabolism on inter-ictal SPECT 48 have been reported in PNES. Several studies have also described patients developing new-onset PNES or somatoform disorders following epilepsy surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary interictal SPECT studies have shown a normal distribution of brain perfusion in PNES patients 10 11. Electroencephalographic approaches have been largely limited to routine clinical EEG and EEG-video monitoring considered as a gold standard for diagnostics 12 13.…”
Section: Introductionmentioning
confidence: 99%